2005
DOI: 10.1073/pnas.0503879102
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of receptor-mediated endocytosis

Abstract: Most viruses and bioparticles endocytosed by cells have characteristic sizes in the range of tens to hundreds of nanometers. The process of viruses entering and leaving animal cells is mediated by the binding interaction between ligand molecules on the viral capid and their receptor molecules on the cell membrane. How does the size of a bioparticle affect receptor-mediated endocytosis? Here, we study how a cell membrane containing diffusive mobile receptors wraps around a ligand-coated cylindrical or spherical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
1,067
3
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,114 publications
(1,154 citation statements)
references
References 30 publications
68
1,067
3
2
Order By: Relevance
“…Nevertheless, models that take a black-box approach to signaling have been used to predict general factors that affect phagocytic behavior. For example, Gao et al (10) and Decuzzi and Ferrari (11) used such models to investigate the effect of ligand density on (nonactin-dependent) endocytosis rates by imagining that particle uptake is passive, driven by the adhesion energy between receptors and ligands (10,11). Richards et al (12) extended these models to phagocytosis by incorporating an active signal (created by progressive receptor binding) that recruits Fc receptors to the phagosome.…”
Section: Characteristics Of Frustrated Phagocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, models that take a black-box approach to signaling have been used to predict general factors that affect phagocytic behavior. For example, Gao et al (10) and Decuzzi and Ferrari (11) used such models to investigate the effect of ligand density on (nonactin-dependent) endocytosis rates by imagining that particle uptake is passive, driven by the adhesion energy between receptors and ligands (10,11). Richards et al (12) extended these models to phagocytosis by incorporating an active signal (created by progressive receptor binding) that recruits Fc receptors to the phagosome.…”
Section: Characteristics Of Frustrated Phagocytosismentioning
confidence: 99%
“…Furthermore, there have been conflicting reports as to whether IgG opsonin density modulates the likelihood that a particle will be fully internalized (8,9). Theoretical models addressing endocytosis (particle internalization not necessarily requiring actin activity) posit that particle internalization rates depend on the ligand density (10)(11)(12). How these predictions relate to actin-driven phagocytosis remains unclear, although it has been proposed that the recruitment of receptors to form phagosomes may contribute to the observed dynamics (12).…”
Section: Introductionmentioning
confidence: 99%
“…During endocytosis, cell membranes with receptors "wrap" around a particle coated with matching ligands. 35 Eleven nm MDP-AuNPs formed clusters in order to enter the cell. This is compatible with the models developed to understand the dynamics of endocytosis such that a single NP smaller than 50 nm does not produce enough free energy to completely wrap the membrane around the NPs.…”
Section: Resultsmentioning
confidence: 99%
“…This is compatible with the models developed to understand the dynamics of endocytosis such that a single NP smaller than 50 nm does not produce enough free energy to completely wrap the membrane around the NPs. 35 Hence, the nanoparticles were mainly clustered in order to be uptaken by the cells. Understanding the mechanisms of internalization is critical to design nanoparticles precisely for specific purposes.…”
Section: Resultsmentioning
confidence: 99%
“…46,47 In regard to this theory, Yoo et al reported a rod-shaped comb-type aptamer-siRNA chimera. 48 In this study, a mucin 1 (MUC1) targeting DNA aptamer was conjugated to the siRNA.…”
Section: Aptamers As Tools For Sirna Deliverymentioning
confidence: 99%